Connecting Arts and Place Cultural Policy and American Cities - Redaelli, Eleonora; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
In this book, Eleonora Redaelli investigates the arts in American cities, providing insight into urban cultural policy discourse through the lens of space. By unpacking the ways in which scholars and policymakers account for geographic configuration and spatial relation, this monograph presents a unique approach to the arts and public policy. Redaelli analyses five main concepts of the international discourse in cultural policy - cultural planning, cultural mapping, creative industries, cultural districts and creative placemaking - highlighting how each of them contributes to the understanding of how the arts connect with place. Employing a selection of American cities as case, this book is an essential contribution to our understanding of cultural policy and its effects. It will be of interest to students and scholars of sociology, public policy, urban studies, arts management and cultural studies.
1. Introduction: Thinking Spatially in Cultural Policy -- 2. Cultural Planning -- 3. Cultural Mapping -- 4. Creative Industries -- 5. Cultural Districts -- 6. Creative Placemaking -- 7. Conclusions: Connecting Arts and Place in American Cities.
Keywords: Cultural property -- Protection; Culture; Arts; Social policy; Cultural Resource Management; Sociology of Culture; Fine Art; Social Policy